(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In the face of digitalization in the world, the transition of digital economic educational institutions as an organization with an important position in the intellectual development of the country, rapid changes are present in the conditions of necessary bridges. The serious digitization of all the processes that make up the modern educational system and its impact on the teaching method is studied in the next article.